1995
DOI: 10.1148/radiology.197.3.7480729
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer: staging with CT and MR imaging.

Abstract: While the staging accuracy of both CT and MR imaging is only moderate, prediction of tumor resectability is excellent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
113
1
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(124 citation statements)
references
References 0 publications
3
113
1
7
Order By: Relevance
“…It is also accurate in demonstration of direct involvement of other pelvic structures by the ovarian tumour. The peritoneal and lymph nodal spread detection by MRI is comparable to the CT. 28 Long imaging time required for MRI evaluation of entire abdomen and pelvis makes it less suitable. Lack of universal availability, high cost of examination makes this modality impractical for routine study in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It is also accurate in demonstration of direct involvement of other pelvic structures by the ovarian tumour. The peritoneal and lymph nodal spread detection by MRI is comparable to the CT. 28 Long imaging time required for MRI evaluation of entire abdomen and pelvis makes it less suitable. Lack of universal availability, high cost of examination makes this modality impractical for routine study in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, in most UK centres, a residual disease of less than 2 cm remains an acceptable goal. Currently the mainstay of preoperative assessment of such patients with regards to resectability and likelihood of achieving OCR are based on clinical examinations, tumour marker levels and CT findings [8][9][10][11][13][14][15][16]. It is also common practice in UK to administer neo-adjuvant chemotherapy prior to Table 1 Comparison of outcome of mini-laparotomy and laparotomy OCR achieved after full laparotomy OCR not achieved after full laparotomy Total OCR predicted possible on mini-laparotomy 24 (true positive) 3 (false positive) 27 OCR predicted not possible on mini-laparotomy 0 (false negative) 8 (true negative) 8…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found MRI to be more accurate in this regard, especially for lymph node metastases and tumor resectability. 77,78 Contrast-enhanced MRI have been found to have a 92% sensitivity in detecting small peritoneal disease such as those that can be found in the omentum, in the mesentery of the small and large bowel, on the anterior abdominal peritoneal surface, under the diaphragm, and in the paracolic gutters. 77 Prolonged survival after ovarian cancer diagnosis and the success of chemotherapy depends on optimal debulking at the time of the initial surgery, yet less than 50% of ovarian cancer patients acquire a gynecologic oncologist to be involved in their care.…”
Section: Gynecologic Malignanciesmentioning
confidence: 99%